2018
DOI: 10.1007/s00787-018-1126-z
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral activation for children and adolescents: a systematic review of progress and promise

Abstract: Behavioral activation (BA) effectively treats depression in adults, and shows promise in treating anxiety. Research into its application to children and adolescents is emerging. This review aimed to explore the scope of studies, current evidence of effectiveness and how the intervention has been delivered and adapted, to inform future research. A systematic review was undertaken searching PsycInfo, PubMed including Medline, EMBASE, and Scopus for terms relating to BA and children and adolescents. Two researche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
57
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(66 citation statements)
references
References 82 publications
5
57
0
1
Order By: Relevance
“…Rumination also interferes with the ability to fully engage in optimal activities, thereby minimizing or reducing positive psychological benefits from work and leisure activities (e.g., Peifer et al 2015;Rusting and Nolen-Hoeksema 1998). For example, greater depression is associated with less engagement in daily activities that bring pleasure (e.g., McAndrew et al 2017) and behavioral activation, the encouragement of becoming more active and engaged in life, is a useful intervention strategy for people experiencing dysphoria and depression (e.g., Chartier and Provencher 2013;Martin and Oliver 2018;Soucy et al 2013). Previous studies have also shown that the quiet ego is negatively associated with measures of depression and anxiety (Collier and Wayment 2019b; Wayment and Brookshire 2018; Wayment and Silver 2018; Wayment and Walters 2017).…”
Section: Arousal and Positive Mood During Diymentioning
confidence: 99%
“…Rumination also interferes with the ability to fully engage in optimal activities, thereby minimizing or reducing positive psychological benefits from work and leisure activities (e.g., Peifer et al 2015;Rusting and Nolen-Hoeksema 1998). For example, greater depression is associated with less engagement in daily activities that bring pleasure (e.g., McAndrew et al 2017) and behavioral activation, the encouragement of becoming more active and engaged in life, is a useful intervention strategy for people experiencing dysphoria and depression (e.g., Chartier and Provencher 2013;Martin and Oliver 2018;Soucy et al 2013). Previous studies have also shown that the quiet ego is negatively associated with measures of depression and anxiety (Collier and Wayment 2019b; Wayment and Brookshire 2018; Wayment and Silver 2018; Wayment and Walters 2017).…”
Section: Arousal and Positive Mood During Diymentioning
confidence: 99%
“…It is also true that the CATCH-IT intervention includes an optional anxiety module (Module #15), which addresses symptoms of anxiety more directly and provides instructions for exercises such as progressive muscle relaxation. Because so few adolescents ( N = 18) in our sample completed the anxiety module, however, it is more likely that the observed improvement in anxiety symptoms is explained by participants’ use of other skills taught in CATCH-IT, such as cognitive restructuring and behavioral activation, both of which are commonly used to treat symptoms of anxiety in adolescents [ 66 , 67 , 68 ].…”
Section: Discussionmentioning
confidence: 99%
“…Decades-old techniques used in psychotherapy sessions are being adapted to the digital context, enabling the delivery of interventions that are automated or partially mediated by a mental health professional. An interesting example is the case of behavioral activation, an intervention designed to help depressed patients identify, schedule, and engage in positive and productive activities to address lack of positive reinforcement and behaviors of avoidance (Martin and Oliver 2018). While in one-on-one psychotherapy sessions behavioral activation is highly customized, taking into account numerous characteristics, such as symptomatology and life aspects, it can be simplified and adapted into apps due to its inherent simplicity.…”
Section: Mobile Applications and Botsmentioning
confidence: 99%